Effects of gyroscopic coupling and countertorque in a fixed-wing nano air vehicle - Pushpangathan, Jinraj V. (2019)
For the nonlinear equations of motion of the nano air vehicle, including the gyroscopic coupling and countertorque generated by the propulsion system, a linear state-space model is developed for analyzing the effects of gyroscopic coupling and countertorque on the dynamic behavior of the nano air vehicle. By analyzing the trajectories of eigenvector components obtained by increasing the gyroscopic coupling, it is shown that the different modes of the nano air vehicle influence both the lateral and longitudinal variables, thereby losing the conventional characteristics of these modes. The investigation shows that the stability of the coupled phugoid and coupled Dutch roll modes are improved, whereas the stability of the coupled spiral, coupled roll subsidence, and coupled short-period modes are degraded with the enhancement of gyroscopic coupling. Concurrently, increasing the gyroscopic coupling increases the damping ratio of the coupled Dutch roll and coupled phugoid modes. In contrast to this, the gyroscopic coupling reduces the damping ratio of the coupled short-period mode. The frequency of the coupled phugoid and coupled short-period modes is also increased with the increment in the gyroscopic coupling. The analysis also indicates that the countertorque destabilizes the coupled spiral mode.